Vibration problems ICOVP 2011 the 10th International Conference on vibration problems - International Conference on Vibration Problems Prague, Czech Republic) 2011; Náprstek, Jiří (Dordrecht, Netherlands Springer Dordrecht, 2011)
This volume presents the Proceedings of the 10th International Conference on Vibration Problems, September 5-8, 2011, Prague, Czech Republic. Since they started in 1990 the ICOVP conferences have matured into a reference platform reflecting the state-of-the-art of dynamics in the broadest sense, bringing together scientists from different backgrounds who are actively working on vibration-related problems in theoretical, experimental and applied dynamics, thus facilitating a lively exchange of ideas, methods and results. Dynamics as a scientific discipline draws inspiration from a large variety of engineering areas, such as Mechanical and Civil Engineering, Aero and Space Technology, Wind and Earthquake Engineering and Transport and Building Machinery. Moreover, the basic research in dynamics nowadays includes many fields of theoretical physics and various interdisciplinary subject areas. ICOVP 2011 covers all branches of dynamics and offers the most up-to-date results and developments in a high-quality selection of 110 papers, with contributors and participants from 40 countries, representing a well-balanced overview
Electronic reproduction.
Keywords: Vibration -- Congresses